Remnant cholesterol contributes to residual lipid risk after acute coronary syndromes. (3rd October 2022) - Wenzl, F; Kraler, S; Raeber, L; Von Eckardstein, A; Matter, C; Gencer, B; Nanchen, D; Rodondi, N; Mach, F; Luescher, T
Abstract: Background: Increasing evidence indicates that cholesterol transported in triglyceride-rich lipoproteins (remnant cholesterol) is a causal risk factor for major adverse cardiovascular events (MACE) independent from other lipid fractions. To date, the relationship between remnant cholesterol (remnant-C) levels and cardiovascular (CV) outcomes after acute coronary syndromes (ACS) in patients with adequate low-density lipoprotein cholesterol (LDL-C) control is uncertain. Purpose: This study evaluated the contribution of remnant-C to residual lipid risk after ACS. Methods: Nested within 4'787 ACS patients in the prospective multicentre SPUM-ACS study (NCT0100070) we examined all patients presenting with LDL-C levels <100 mg/dl under lipid lowering therapy (n=756). Remnant-C was calculated as non-high-density lipoprotein cholesterol (non-HDL-C) minus calculated LDL-C using the Martin/Hopkins modified equation. The predefined primary outcome was a composite of CV death, myocardial infarction, and ischemia-driven revascularization at 12 months. Events were adjudicated by an independent external endpoint committee blinded to the lipid measurements. Multivariable-adjusted Cox models were fitted using smoothing splines for absolute remnant-C levels (continuous), log-transformed absolute remnant-C levels (continuous), remnant-C tertiles (categorical) and a prespecified cutoff (75th percentile) for high remnant-C (categorical). Bias-corrected bootstrapping was used for internal validation. Results: Eighty-seven (11.5%) patients had an event, 14 (1.9%) patients withdrew consent, and 5 (0.7%) patients were lost to follow up at 12 months. In multivariable-adjusted analyses, remnant-C (hazard ratio [HR]: 1.63; 95% confidence interval [CI]: 1.04 to 2.74; per log2 increase; p=0.020), triglycerides (HR: 1.41; 95% CI: 1.04 to 1.96; per log2 increase; p=0.017), and low high-density lipoprotein (HDL)-C (HR: 0.56; 95% CI: 0.33 to 0.86; per log2 increase; p<0.040), but not LDL-C (HR: 1.41; 95% CI: 0.78 to 2.84; per log2 increase; p=0.272), were associated with MACE. High remnant-C was independently associated with elevated risk of MACE when adjusting for clinical and demographic factors including GRACE 2.0 risk estimates (HR: 2.43; 95% CI: 1.42 to 4.27; above vs. below 75th percentile; p<0.001; HR: 2.10; 95% CI: 1.09 to 4.70; tertile 3 vs. tertile 1; p=0.014). Conclusion: In patients who develop ACS with LDL-C levels <100 mg/dl, levels of remnant-C and triglycerides, but not LDL-C, were associated with adverse CV outcomes independent of other risk factors. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Swiss National Science FoundationSwiss Heart Foundation